2012
DOI: 10.1002/chem.201200899
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Tetragonal Cu2Se Hyperbranched Structures: Large‐Scale Preparation and Tunable Electrical and Optical Response Regulated by Phase Conversion

Abstract: Despite the promising applications of copper selenide nanoparticles, an in-depth elucidation of the inherent properties of tetragonal Cu(2)Se (β-Cu(2)Se) has not been performed because of the lack of a facile synthesis on the nanoscale and an energy-intensive strategy is usually employed. In this work, a facile wet-chemical strategy, employing HCOOH as reducing agent, has been developed to access single-crystalline metastable β-Cu(2)Se hyperbranched architectures for the first time. The process avoids hazardou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 63 publications
3
29
0
Order By: Relevance
“…An example is the cuprous selenide (Cu 2 Se) nanoparticles, which are easily oxidized into non-stoichiometric Cu 1.8 Se, and become into surprisingly good p-type semiconductor with over 3000 times of enhancements in electrical conductivity. [2] In order to tune the properties of nano-scale copper selenides, a number of techniques and strategies, such as hydro-or solvo-thermal approach, [2,15,16] sonochemistry, [17] electrochemical-deposition, [18] microwave-assistant route, [19] ball milling technique, [6] and chemical welding method, [5] have been developed to prepare nanocrystals, [20] nanotubes/wires, [15,[21][22][23] nanocages, [24] dendrimers, [16,25] and nanosheets [26] with well-defined size, morphology, crystal structure, and composition.…”
Section: Introductionmentioning
confidence: 99%
“…An example is the cuprous selenide (Cu 2 Se) nanoparticles, which are easily oxidized into non-stoichiometric Cu 1.8 Se, and become into surprisingly good p-type semiconductor with over 3000 times of enhancements in electrical conductivity. [2] In order to tune the properties of nano-scale copper selenides, a number of techniques and strategies, such as hydro-or solvo-thermal approach, [2,15,16] sonochemistry, [17] electrochemical-deposition, [18] microwave-assistant route, [19] ball milling technique, [6] and chemical welding method, [5] have been developed to prepare nanocrystals, [20] nanotubes/wires, [15,[21][22][23] nanocages, [24] dendrimers, [16,25] and nanosheets [26] with well-defined size, morphology, crystal structure, and composition.…”
Section: Introductionmentioning
confidence: 99%
“…All these phases are identified as p-type semiconductors due to the existence of copper vacancies within crystal lattice, and widely used in solar cells45, gas sensors6, and photo-detectors7. Instead of crystal phases, efforts have also been devoted to preparing copper selenides with controlled morphologies such as nanoparticles891011, nanocubes1213, nanotubes14, nanowires1516 and hierarchical nanostructures1718.…”
mentioning
confidence: 99%
“…[16] Additionally, Cu 2 Se is prone to oxidation into more thermodynamically stable nonstoichiometric copper chalcogenide phases. In the present case, we used TOP as an extraction agent, reducing agent, and stabilizing agent and it can cause hexagonal CuSe and cubic Cu 2-x Se to readily convert to monoclinic Cu 2 Se at 220°C.…”
Section: Resultsmentioning
confidence: 99%
“…Copper selenides exhibit particular optical, superionic, thermoelectric, and photoelectric properties and considerable progress has been made on their applications in electronic and optoelectronic devices. [16] However, no studies of the SERS performance of copper selenide based materials have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation